2015
DOI: 10.1093/chromsci/bmv043
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization of a Potential Degradation Product of Aspirin and an HPLC Method for Quantitative Estimation of Its Impurities

Abstract: In this work, a new degradation product of Aspirin was isolated, characterized and analyzed along with other impurities. New unknown degradation product referred as UP was observed exceeding the limit of ICH Q3B identification thresholds in the stability study of Aspirin and Dipyridamole capsule. The UP isolated from the thermal degradation sample was further studied by IR, Mass and (1)H NMR spectrometry, revealing structural similarities with the parent molecule. Finally, UP was identified as a new compound g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Dipyridamole is an accessory to oral anticoagulation for thromboembolism prophylaxis associated with prosthetic heart valves. It was intended to treat blood clot formation by reducing platelets and endothelial adenosine uptake, which reduces the stimulation of both platelet activating and collagen factors by promoting cyclic adenosine monophosphate (cAMP) accretion (Bult et al, 1991). It is chemically named as 2-[2-[bis(2-hydroxy-ethyl)amino]-4,8di(piperidin-1yl)pyrimido [5,4-d]pyrimidin-6yl]-(2-hydroxy-ethyl) amino ethanol and the chemical structure of dipyridamole (Yogesh et al, 2012) is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dipyridamole is an accessory to oral anticoagulation for thromboembolism prophylaxis associated with prosthetic heart valves. It was intended to treat blood clot formation by reducing platelets and endothelial adenosine uptake, which reduces the stimulation of both platelet activating and collagen factors by promoting cyclic adenosine monophosphate (cAMP) accretion (Bult et al, 1991). It is chemically named as 2-[2-[bis(2-hydroxy-ethyl)amino]-4,8di(piperidin-1yl)pyrimido [5,4-d]pyrimidin-6yl]-(2-hydroxy-ethyl) amino ethanol and the chemical structure of dipyridamole (Yogesh et al, 2012) is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is chemically named as 2-[2-[bis(2-hydroxy-ethyl)amino]-4,8di(piperidin-1yl)pyrimido [5,4-d]pyrimidin-6yl]-(2-hydroxy-ethyl) amino ethanol and the chemical structure of dipyridamole (Yogesh et al, 2012) is shown in Figure 1. The analytical methods reported include high-performance liquid chromatography (HPLC) analysis of dipyridamole (Bridle et al,1993;Fontani et al, 1983;Hassan et al, 2008;Rao et al, 2016); reverse-phase high-performance liquid chromatography (RP-HPLC) stability, indicating the method for dipyridamole and its impurities (Acharya et al, 2015;Vaghela et sal., 2012); method development and validation for dipyridamole and aspirin by HPLC (Zhang et al, 1997); HPLC methods to identify dipyridamole in human plasma (Barberi et al, 2006); and stability-indicating RP-UPLC in combined capsule formulation (Rajput et al, 2011), revealing the simultaneous determination of dipyridamole and aspirin. Only HPLC methods were reported to determine dipyridamole and there is no UPLC-Q-TOF-MS (ultraperformance liquid chromatography to quadrupole time-of-flight mass spectrometry) analytical approach for the identification of impurities in dipyridamole literature sources.…”
Section: Introductionmentioning
confidence: 99%